Indigenous peoples and modernity. - DURSTON, John (1993)
Analyses the implications of culture, knowledge and modernity in terms of a more forceful role for the indigenous peoples of Latin America. Notes that the relationship between culture and economic development is still very poorly understood. Points out that increased productivity based on the incorporation of universal knowledge is not only compatible with the maintenance of a people's own culture, but is actually essential for an increase in output to result in a higher real level of well-being for the population.